Agrometeorological Conditions and Agroclimatic Trends for the Maize and Wheat Crops in the Balkan Region - Ioannis Charalampopoulos (Atmosphere, 2021)
The Balkan peninsula is a transitional zone, in terms of bioclimatic conditions, with an extended and dynamic agricultural sector. Its potential is in peril due to climate change and socioeconomic factors. To assess and evaluate the agrometeorological conditions and the related trends which affect the widely cultivated wheat and maize, a big dataset with high spatiotemporal analysis was utilized. The thermal indices of Growing Degree Days (GDD) and Heat Stress Index (HSI) along with the main frost parameters (frost days, last spring frost, first autumn frost, and free of frost days) were calculated over ten countries for 42 years on a daily basis over a grid of 25 × 25 km. The results indicate a clear cultivations’ expansion ability to northern areas, and higher altitudes and an increased risk of heat caused plants’ injuries. The thermal indices’ trends for maize and wheat cultivation are always positive (Maize: GDD 7.26–11.05 units/yr, HSI 0.52–3.51 units/yr Wheat: GDD 7.2–12.7 units/yr, HSI 0.22–1.77 units/yr). The free of frost (FFD) season is getting longer (trend −0.04 to 0.34 d/yr) because of earlier last spring frost and delayed first autumn frost. The results consist of spatial and temporal illustrations, along with summary statistics and probability density plots for the entire study area and per country.